Odpowiedź :
Odpowiedź:
3x+[tex]\frac{5}{4}[/tex]-2x+[tex]\frac{2}{8}[/tex]=[tex]\frac{1}{2}[/tex]*(3-x)
3x+[tex]\frac{5}{4} -2x+\frac{1}{4}[/tex] = [tex]\frac{3}{2} -\frac{1}{2}[/tex]x |+[tex]\frac{1}{2}[/tex]x
3x+[tex]\frac{5}{4}[/tex]-2x+[tex]\frac{1}{4}[/tex]+[tex]\frac{1}{2}[/tex]x=[tex]\frac{3}{2}[/tex] |-[tex]\frac{5}{4}[/tex]-[tex]\frac{1}{4}[/tex]
3x-2x+[tex]\frac{1}{2}[/tex]x=[tex]\frac{6}{4} - \frac{5}{4}[/tex] - [tex]\frac{1}{4}[/tex]
1 [tex]\frac{1}{2}[/tex]x=0 |:1[tex]\frac{1}{2}[/tex]
x=0
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]3x+5 \div 4-2x+2÷8=1÷2×(3-x) \\
3x+1,25-2x+0,25 = \frac{1}{2} ×(3-x) \\ x + 1.25 = \frac{3}{2} - \frac{1}{2}x \\ x + \frac{3}{2} = \frac{3}{2} - \frac{1}{2}x \\ 2x + 3 = 3 - x \\ 2x = - x \\ 2x + x = 0 \\ 3x = 0 \\ x = 0[/tex]
Szczegółowe wyjaśnienie:
liczę na naj